(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
A study has supported the idea of this system dependent on a transnational legal positivism study. Conversely, others, in view of an absence of fundamental characteristics of law and basic inadequacies in international arbitration, will not remember it as a self-ruling legal system. The principle target of the present work is to ponder the major legal hypotheses about the legality and systematicity of international commercial arbitration, and after that to take a review of the unfavourable and beneficial results of applying the idea of the arbitral legal system. This development has created a dynamic exchange over the legality and systematicity of the arbitral legal system. By applying different legal hypotheses, researchers of various legal systems have examined the legality of the arbitral legal system.